Traditional Chinese Medicine is an Alternative Therapeutic Option for Treatment of Pseudomonas aeruginosa Infections - Pang, Zheng; Zhu, Qingjun (Frontiers in Pharmacology, 2021)
Pseudomonas aeruginosa is an opportunistic pathogen causing life-threatening infections in cystic fibrosis patients and immunocompromised individuals, and it is a leading cause of nosocomial infections associated with significant morbidity and mortality. Treatment of P. aeruginosa infections is challenging due to its antibiotic resistance to most of the conventional antibiotics. Development of alternative therapeutic options is urgently demanded for the patients who have antibiotic-resistant infections. Traditional Chinese medicine (TCM) has a clinical history of thousands of years for prevention and treatment of infectious diseases in China, taking advantage of improving clinical outcome, producing less side effects, inhibiting pathogen, and modulating host immunity. Recent research has revealed a variety of natural products isolated from traditional Chinese medicine showing significant antimicrobial effects on antibiotic-resistant strains of P. aeruginosa alone or combined with antibiotics in vitro or in animal models, suggesting that TCM is a promising complementary and alternative therapeutic approach for treatment of chronic P. aeruginosa infections. This review summarizes the recent findings attempting to dissect the mechanisms of TCM combating P. aeruginosa infections and highlights the molecular targets of TCM on P. aeruginosa and host.